2016
DOI: 10.1371/journal.pone.0163080
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Designed TNF-α Epitope-Scaffold Immunogen Induces Sustained Antibody Response and Alleviates Collagen-Induced Arthritis in Mice

Abstract: The TNF-α biological inhibitors have significantly improved the clinical outcomes of many autoimmune diseases, in particular rheumatoid arthritis. However, the practical uses are limited due to high costs and the risk of anti-drug antibody responses. Attempts to develop anti-TNF-α vaccines have generated encouraging data in animal models, however, data from clinical trials have not met expectations. In present study, we designed a TNF-α epitope-scaffold immunogen DTNF7 using the transmembrane domain of diphthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Previous studies have shown that DTT can help break immune self-tolerance when an immunogen is fused to its C-terminal [16]. For immunogen specific against mEGFR, both ECD domain II (aa190-334) and domain III (aa335-505) are considered as they are functionally important for the receptor activation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that DTT can help break immune self-tolerance when an immunogen is fused to its C-terminal [16]. For immunogen specific against mEGFR, both ECD domain II (aa190-334) and domain III (aa335-505) are considered as they are functionally important for the receptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…In order to mimic the native conformation of the epitope peptide, we grafted the peptide onto the DTT at positions aa 88-94 that has been shown an ideal site for epitope presentation [16]. EGFR 265-283 is grafted to minimize structural perturbation of the carrier DTT, according to the method of Li Zhang et al [16]. To achieve higher anti-tumor efficacy of the vaccine, we considered fusion of ECD subdomain III to the C-terminal of DEGFR p .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations